An Analysis of the Effects of Brexit on Korean SMEs - kim, daejong (Archives of Business Research, 2018)
The purpose of this paper is to examine the impact on Korean SMEs after the Brexit . . The research method used an industry association analysis. The results of the study are as follows. First, total exports in 2015 were 519.9 billion, while exports to the UK were 7.4 billion. Exports to the UK are about 1.4% of Korea’s total exports. The amount of damage to the total gross domestic product of Korea is estimated to be about 1.6 trillion won. SMEs account for about 56% of the total manufacturing output in Korea and about 12% of UK exports. Second, the loss estimate for SMEs is estimated to be W940bn. The amount of about 1 trillion won is a large amount, so anyone potentially affected will have to prepare. Policy implications are as follows: First, SMEs should move from export-oriented management to domestic-oriented management. Second, the export window should be unified to help SMEs export. The significance of this paper is to analyze the impact of small firms on SMEs.